Role of Physician’ Characteristics in Drug Prescription: Evaluation From Drug Database in Improving Prescribing Regulation - Flori R. Sari; Saiful Anwar; Risahmawati Risahmawati; Marita Fadhilah; Fika Ekayanti (The Avicenna Medical Journal, 2023)
Introduction: Drugs prescribing is the most important skill for physicians and is strictly regulated by the government. However, factors that contribute to the drug prescribing are not determined yet. The aim of this study is to identify the possible role of physician character in drug prescribing at primary health centers (PHC).Method: A cross-sectional study was purposely done over fourteen-days at PHCs of Tangerang Districts. All prescriptions (n=2410) registered in the PHC drug-alert system (CIDIA Database) were analyzed descriptively.Result: From 2410 prescriptions registered in the PHC drug alert system, 15% prescriptions were prescribed by male physicians and 85% by the females. During the study, there were 964 drugs prescribed by 6 male physicians, 161 drugs per physician in average. There were 5584 drugs prescribed by 12 female physicians, 465 drugs per physician on average. Female physicians tended to prescribe 4 or more drugs compared to its male counterpart at 14% (p=0.006). However, there was no significant difference of drug interactions observed in the prescriptions prescribed by male or female physicians (p>0.05).Discussion: We identified that physician characteristics including gender played a significant role in the drug prescribing process especially the number of drugs prescribed. Therefore, considering gender differences in prescribing drugs may help the PHCs to improve a better management in drug safety and to comply with the government prescribing regulation.